Effective Writing Instruction for Students in Elementary Level Who Find Writing Challenging: Evidence-Based Practices - Sapkota, Sangita; Gnawali, Laxman (The Harvest, 2025)
Writing is a crucial skill for academic and professional attainment, yet it remains neglected in literacy instruction. The negligence, along with inadequate instruction, makes writing more challenging for elementary students who have lower writing proficiency. To identify evidence-based practices of writing instruction, this article systematically reviews the latest literacy studies on writing instruction. Using four databases; EBSCOHost, Education Research Complete, ERIC, and Teacher Reference Center, with certain Boolean phrases, eight studies meeting inclusion criteria are selected. The article is a synthesis of findings across the eight studies reviewed. Different themes are created incorporating commonalities and unique findings and are discussed through the lens of the SRSD Model. Multiple strategies such as spontaneous prompting with instructional feedback, explicit instruction, mnemonic strategies, morphological word knowledge instruction, and technology instruction are evidence-based practices of writing instruction as they are proven to boost students’ confidence, clarity, and the quality of writing. While, this review provides a general overview of writing strategies, future research could emphasize exploring effective strategies for teaching specific aspects/ areas of writing instruction, for instance, a synthesis of the strategies for teaching vocabulary or genre-specific writing.